DEVELOPMENT OF STUDENTS' ABILITY TO USE INFORMATION TECHNOLOGIES IN EDUCATION (International journal of artificial intelligence, 2024)
This article explores the importance of developing students' ability to use information technologies (IT) in the educational process. It discusses how IT tools, such as computers, multimedia, online learning platforms, and collaboration tools, play a crucial role in enhancing student engagement, fostering critical thinking, and preparing students for a technology-driven future. The article highlights key areas where IT is integrated into education, including digital literacy, interactive learning, and collaboration, and emphasizes the need for strategies to help students acquire these essential skills. It also examines the role of educators in facilitating IT learning and offers suggestions for integrating technology into curricula effectively. Ultimately, the article demonstrates how developing IT skills not only enhances academic performance but also equips students with the necessary competencies for the modern workforce.